Charging and Sentencing of Murder and Voluntary Manslaughter Cases in Georgia, 1973-1979 - Baldus, David C. ([Verlag nicht ermittelbar], 1989)
These data were collected to assess the levels of racial discrimination and arbitrariness occurring at different levels within Georgia's capital charging and sentencing system. Data cover approximately 1,000 murder and voluntary manslaughter cases. Information was obtained for all known penalty trial cases and for certain cases stratified by case type (voluntary manslaughter conviction, nonpenalty trial life sentence, and penalty trial) and by state judicial circuit. Numerous measures of defendant blameworthiness were developed as a basis for assessing levels of arbitrariness and discrimination in the capital charging and sentencing system. Variables include race, sex, and socioeconomic class, as well as crime codes, jury/bench decisions, final plea, term, and number of counts convicted.